Advancing a cross-cultural narrative approach to career counselling: The case of Vietnam. (July 2018) - Nguyen, Lan Thi; McDonald, Matthew; Mate, Susan; Taylor, Greig
The purpose of this paper is to advance the concept of narrative approaches to career counselling from a cross-cultural perspective by investigating the case of Vietnam. It offers an account of the sociocultural context of Vietnam as it shifts from its traditional Confucian and communist values to a modern globally integrated market economy. Current approaches to career counselling in Vietnam for students in secondary and tertiary education are outdated and so fail to respond to the challenges that this shift is creating. It is argued that narrative career counselling has the potential to reconcile the tension between the need for flexibility and self-direction in work and career in a society that continues to be heavily influenced by Confucian ethics and collective notions of the self. The paper concludes with a call for future research on the practice of narrative career counselling cross-culturally to test its suitability.